Avaliação da atividade dos canais para sódio dependentes de voltagem dos neurônios do gânglio da raiz dorsal na dor em modelagem computacional - Silva, Kelly Coutinho da (2022)
The ability to detect noxious stimuli is essential for an organism’s survival and well-being. Pain information is generated through activation of nociceptors, which are receptors located in the periphery. These nociceptors are the most distal part of the primary afferent neurons and correspond to the narrowest portions of the fibers that carry messages originating after a noxious stimulus. Primary afferent neurons synapse with second-order neurons in the dorsal horn of the spinal cord. Several studies report the importance of voltage-gated sodium channels for the excitability of these peripheral cells and the transmission of pain signals. Some of these researches have used new technologies such as computational modeling to anticipate results that will be later tested in vitro or in vivo. Therefore, this study aimed to evaluate the participation of voltage-dependent sodium channels in dorsal root ganglion cells in pain using conductance-based computational neuron models. To evaluate the action of these channels in small and large cells of the dorsal root ganglion, parameters such as rheobase, chronaxis, input resistance, characteristic time τ , interval between action potentials, firing rate, amplitude of action potentials and action potential width. The results of the work showed that the presence of the N av1.1 subtype in the cell promotes a reduction of the input resistance and of the characteristic time and its absence promotes anticipation of the generation of the action potential and in the cells of smaller caliber favoring the formation of high frequency shots with the increase in the applied stimulus, the absence of N av1.2 in the large-caliber cells anticipated the formation of action potential and in the small-caliber cell, it increased the time for the membrane to return to rest, in addition to reducing the amplitude of the shots. The N av1.3 channel promoted a significant increase in the firing amplitude and the removal of this channel from the large-caliber cell caused an increase in the time to return to rest, whereas in the small-caliber cells, this removal facilitated the formation of high-frequency firings, but with potentials with smaller amplitudes. The N av1.6 isoform was the one that promoted changes in most of the parameters evaluated, after subtraction of the neuron channel there was an increase in rheobase, potential width, trigger amplitude, reduction of chronaxie, input resistance, time characteristic and for all cell sizes favored the formation of high frequency shots. The removal of subtypes N av1.7, N av1.8 and N av1.9 facilitated the occurrence of high frequency potentials. It can be seen that voltage-gated sodium channels play an important role in activating the membrane of dorsal root ganglion cells and that some channels are specifically related to cell excitability and the amplitude of firing, which directly influence the transmission of stimuli between the periphery and secondary neurons for further processing of pain in the central nervous system.